الصلابة النفسية لدى الامهات اطفال التوحد دراسة ميدانية بالمراكز النفسي البيداغوجي للمعاقين ذهنيا بالاغواط قدور بساس دراسة ثلاث حالات - غنية لجرب; مصطفى صفراني; سيحيري زينب (My University, 2023)
This study aims to reveal the level of psychological toughness among mothers of autistic children who are cared for by the psychological and pedagogical center for the mentally disabled in the state of Laghouat. Our study began from a main question as follows: - What is the level of psychological toughness among mothers of children with autism spectrum disorder?? To answer this question, we used the clinical approach and case study, and relied on data collection tools represented in: clinical observation, semi-directed clinical interview, and the psychological hardiness questionnaire by Imad Mkhaimer (2002), standardized on the Algerian environment by Professor “Bachir Maamria” (2011). Our study included 03 cases of mothers of autistic children, and the results of this study reached: There is a moderate level of psychological hardiness among mothers of autistic children. - There is a moderate level of commitment among mothers of autistic children. -There is a moderate level of control among mothers of autistic children. -There is a moderate level of challenge among mothers of autistic children. Keywords: psychological hardiness, autism, mothers of autistic children.Yes, there is a relationship between psychological hardness and marital support Keywords: psychological hardiness, autism, mothers of autistic children